2015
DOI: 10.3139/105.110272
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Fine and Coarse Grain Layer by Atmosphere Control in Case Hardening*

Abstract: Grain coarsening can cause decrease of the fatigue strength of carburized steel components. This artefact is considered to derive from a change in crack-initiation behaviour at the surface. However, grain coarsening can increase the hardenability of steel and thereby avoid the addition of alloying elements bringing about such hardenability. Thus, it is expected that steel with a dual-layer structure of a fine grain layer at the surface and a coarse grain layer in the inside achieves good fatigue strength and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Many studies [11][12][13] showed that titanium could form tiny and distributed dispersively carbonitride with high-temperature thermal stability in steel, which can pin grain boundary in the austenite growth process and then refine the grain size. Although grain refinement will reduce the hardenability of 20CrMnTi gear steels [4,14], the effect of grain refinement on the periphery hardness uniformity of end-quenched specimens has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [11][12][13] showed that titanium could form tiny and distributed dispersively carbonitride with high-temperature thermal stability in steel, which can pin grain boundary in the austenite growth process and then refine the grain size. Although grain refinement will reduce the hardenability of 20CrMnTi gear steels [4,14], the effect of grain refinement on the periphery hardness uniformity of end-quenched specimens has not been reported.…”
Section: Introductionmentioning
confidence: 99%